2016
DOI: 10.1002/iid3.93
|View full text |Cite
|
Sign up to set email alerts
|

Bovine leukemia virus reduces anti‐viral cytokine activities and NK cytotoxicity by inducing TGF‐β secretion from regulatory T cells

Abstract: CD4+CD25highFoxp3+ T cells suppress excess immune responses that lead to autoimmune and/or inflammatory diseases, and maintain host immune homeostasis. However, CD4+CD25highFoxp3+ T cells reportedly contribute to disease progression by over suppressing immune responses in some chronic infections. In this study, kinetic and functional analyses of CD4+CD25highFoxp3+ T cells were performed in cattle with bovine leukemia virus (BLV) infections, which have reported immunosuppressive characteristics. In initial expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…In the advanced stages of BLV infection, BLV-specific Th1 responses are downregulated, leading to further disease progression and possible EBL (31). Several previous studies have demonstrated that loss of BLV-specific Th1 responses is mediated by upregulation of immunoinhibitory molecules such as PD-1 and PD-L1, as well as by expansion of regulatory T cells (15,16,24). Similarly, our previous study revealed that PGE 2 suppresses Th1 responses, such as T cell proliferation and Th1 cytokine production, and induces the expression of PD-L1 (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the advanced stages of BLV infection, BLV-specific Th1 responses are downregulated, leading to further disease progression and possible EBL (31). Several previous studies have demonstrated that loss of BLV-specific Th1 responses is mediated by upregulation of immunoinhibitory molecules such as PD-1 and PD-L1, as well as by expansion of regulatory T cells (15,16,24). Similarly, our previous study revealed that PGE 2 suppresses Th1 responses, such as T cell proliferation and Th1 cytokine production, and induces the expression of PD-L1 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Infection was confirmed by detection of the provirus using nested PCR targeting the viral long terminal repeat (16) and by detection of the anti-BLV Ab using a commercial ELISA (JNC, Tokyo, Japan). The leukocyte numbers in BLVinfected cattle were counted using a Celltac a MEK-6450 automatic hematology analyzer (Nihon Kohden, Tokyo, Japan), and animals were classified as AL or PL as described previously (24). PBMCs derived from these blood samples were purified by density gradient centrifugation on Percoll (GE Healthcare, Buckinghamshire, U.K.) and cultured in RPMI 1640 (Sigma-Aldrich, St. Louis, MO) supplemented with 10% heat-inactivated FCS (Thermo Fisher Scientific, Waltham, MA), 100 U/ml penicillin, 100 mg/ml streptomycin, and 2 mM L-glutamine (Thermo Fisher Scientific).…”
Section: Cell Preparationmentioning
confidence: 99%
“…In some cases, no synthesis of the corresponding antibodies is revealed in BLV-infected animals, despite the presence of the integrated proviral DNA [17]. BLV infection is shown to inhibit the regulatory function of T-lymphocytes subpopulation (CD4 + CD25 high Foxp3+) resulting in suppression of antiviral activity, particularly in NK-cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of Treg cells positively correlates with the number of lymphocytes, the virus titer and viral load in BLV infected cattle. There is experimental data showing that suppression of antiviral activity and cytotoxicity of NK-cells is due to activation of the secretion of growth-transforming beta factor (TGF-β) by Treg cells [22]. It should be emphasized that one of the effects of BLV proviral gene tax on host genes is an increase in the expression of tumor necrosis factor TNF- [23,24], which, in turn, activates Treg cells [25,26].…”
Section: Expression Of Genes Nk-lysin Blvr Ifn- In Peripheral Bloomentioning
confidence: 99%